Visualization of intergroup relations research: a bibliometric analysis based on CiteSpace - Yao, Shujing; Mohd Khir, Azlina; Ma’rof, Aini Azeqa; Wan Jaafar, Wan Munira (Universiti Putra Malaysia, 2025)
This study conducted a bibliometric analysis of intergroup relations literature using CiteSpace 6.3.R1 to examine 2,774 articles from the Web of Science Core Collection (2014–2024). Bibliometric methods like keyword co-occurrence, co-citation, and cluster analysis were used to identify trends, hotspots, and emerging themes. The findings reveal a general trend of increasing publication volume, with the United States, the United Kingdom, and the Netherlands identified as the most active contributors. Key research topics include "prejudice," "intergroup contact," and "identity," while emerging themes such as "racial attitudes," "group threat," "social change," and "adolescence" indicate the dynamic evolution of the field. This study highlights the dual characteristics of foundational and applied research in intergroup relations, emphasizing its interdisciplinary potential and practical relevance. By mapping the knowledge structure of the field, the findings provide valuable insights for scholars and policymakers to address pressing societal challenges, such as reducing prejudice, fostering social inclusion, and mitigating intergroup conflicts. Additionally, this study underscores the importance of interdisciplinary approaches and cross-sectoral collaboration in advancing intergroup relations research, offering a roadmap for its future development.